Wear analysis by applying a pin-disc configuration to phemoral head and acetabular cup (2008)
This work determines a prosthetic hip system’s life-span, focusing on a Mexican phenotype. The total sliding equivalent distance for the system was determined, as well as the loading regime under which the femoral component and the acetabular cup were subjected in normal operating conditions. An experimental tribology essay was then performed to simulate the wearing of the components in a Pin over Disc machine. This assay (for which the test specimens were manufactured in medical grade stainless steel AISI-ASTM 316L for the femoral component and high density polyethylene for the acetabular cup) was aimed at simulating wear conditions involved in 10 years of continuous operation. A numerical simulation of operational conditions (using the finite element method) was performedIn for establishing assay loading conditions to accurately determine where the loads should be applied. The tribology assay led to quantifying the volumetric loss of materials for the system being analysed. It can be concluded that the methodology proposed in this work for estimating the life-span of a prosthetic hip system was valid and accurate by comparing the results with those found in the literature. A statistical validation of the proposed method is plaaned for the future. Key words: Design life; femoral component; acetabular cup; Mexican phenotype; pin-disc configuration.